2008
DOI: 10.2166/wst.2008.400
|View full text |Cite
|
Sign up to set email alerts
|

Methane production from ethanol co-products in anaerobic SBRs

Abstract: Methane production from condensed distillers' solubles (CDS, or syrup), a co-product of ethanol production, was studied in 2-l anaerobic sequencing batch reactors (ASBRs) under 10 different operating conditions. Methane production and COD removal were quantified under steady state conditions for a wide range of operating parameters. COD removals of 62-96% were achieved at OLRs ranging from 1.5-22.2 g COD l(-1) d(-1), SRTs from 8-40 d, and F/M ranging from 0.37-1.95 g COD g(-1) VSS d(-1). The methane content of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
(5 reference statements)
0
7
1
1
Order By: Relevance
“…However, for the specific case of corn-toethanol industry, the ERC estimated in this work (7.05e17.41%, Table 4) is significantly lower when compared to data (43e65%) previously reported elsewhere (Stover et al, 1984;Khanal, 2008;Agler et al, 2008;Cassidy et al, 2008;Schaefer and Sung, 2008). Again, at this point the influence of overestimated data should be discussed, since the literature reports values of 6.70 (Nguyen et al, 2007b) and 5.80 MJ L À1 EtOH (Khanal, 2008) for the energetic potential of corn and cassava, respectively.…”
Section: Energy Recovery Capacity Of Methane: Potentials and Limits Icontrasting
confidence: 81%
See 2 more Smart Citations
“…However, for the specific case of corn-toethanol industry, the ERC estimated in this work (7.05e17.41%, Table 4) is significantly lower when compared to data (43e65%) previously reported elsewhere (Stover et al, 1984;Khanal, 2008;Agler et al, 2008;Cassidy et al, 2008;Schaefer and Sung, 2008). Again, at this point the influence of overestimated data should be discussed, since the literature reports values of 6.70 (Nguyen et al, 2007b) and 5.80 MJ L À1 EtOH (Khanal, 2008) for the energetic potential of corn and cassava, respectively.…”
Section: Energy Recovery Capacity Of Methane: Potentials and Limits Icontrasting
confidence: 81%
“…Theoretically, the high organic content found on HSW could be converted into high volumes of methane, such that a minimum-to-average energy recovery capacity (ERC) of 50e60% could be obtained from biogas combustion in industrial plants (Borzacconi et al, 1995). Based on the specific study of AD applied to stillage, previous studies analyzing the corn-to-ethanol industry indicated potential reductions on the consumption of fossil fuels ranging from 43 to 65% in distilleries due to the use of biogas as an energy source (Stover et al, 1984;Khanal, 2008;Agler et al, 2008;Cassidy et al, 2008;Schaefer and Sung, 2008). However, some studies tend to discuss superficially the ERC of methane, being the methane production often characterized as a complementary parameter to assess the treatment performance in anaerobic reactors, usually reported in terms of COD removal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the turn of the century, the size and number of grain ethanol plants increased rapidly and the interest for energy recovery by AD became more and more important (Wilkie et al 2000;Hutnan et al 2003;Gleixner 2007;Drosg et al 2008;Dousková et al 2010). Apart from whole grain stilläge, different stiilage fractions that occur at a dry-grind ethanol plant also became of interest for AD (Khamal et al 2005;Agler et al 2008;Cassidy et al 2008;Schaefer & Sung 2008). Although process integration of whole stiilage has been investigated (van Haandel 2005;Pfeffer et al 2007;Wukovits et al 2007), little information is available for detailed process integration of AD from different stilläge fractions into a bioethanol facility.…”
Section: Anaerobic Digestion As An Alternative Stiilage Treatment Optionmentioning
confidence: 99%
“…This conversion can be achieved through the technology of anaerobic fermentation or digestion. This is a technology that involves the action of microorganisms in the degradation of organic or biological materials in the absence of atmospheric oxygen [4,5]. The process of producing biogas or biomethane through anaerobic fermentation is referred to as biomethanization or biomethanation.…”
Section: Introductionmentioning
confidence: 99%